PENUMBUHAN LAPISAN TIPIS A-SI:H DENGAN METODA HW-PECVD DAN APLIKASINYA PADA TRANSISTOR LAPISAN TIPIS - Ahda, Syahfandi
Abstrct: Development of PECVD (Plasma Enhanced Chemical Vapour Deposition) system to be HW-PECVD (Hot Wire-Plasma Enhanced Chemical Vapour Deposition) has been carried out by the way of the tungsten coil filament placed in front of the sample holder or parallel with the input gas flow, for getting an hydrogenated amorphous silicon (a-Si:H) having the high conductivity. To generate plasma in deposition process was used radio frequency at 16.10 MHz. with using gas source of 10 % silane diluted in hydrogen (H2). Optimizing the growth parameter of the a-Si:H thin film has been done to verify the flow rate of silane from 40 to 80 sccm and the substrat temperature from 175 to 275 Â°C. Measurements of the dark conductivity, photoconductivity and band gap have been evaluated as the growth results. From conductivity measurements for each sample, one of them was obtained the highest dark conductivity of 5,51 x 10-6 S/cm and also the highest photoconductivity of 1,95 x 10-3 S/cm at the flow rate of silane of 50 sccm and the substrat temperature of 275 Â°C. This optimum dark conductivity by using HW-PECVD relatively exhibits higher than the conventional PECVD or HW-CVD (Hot Wire-Chemical Vapour Deposition) by Broguira. Even though the band gap for that parameter was obtained at 1.7 eV. The a-Si:H thin film structure, which was characterized by using x-ray diffraction, showed the amorphous structure indicated with no intensity peak exists: The hydrogen contents qualitatively were determined using FT-IR technique and the results exhibited hydrogen contents decrease was as the substrat temperature increase. The a-Si:H thin film at the highest conductivity was applied on thin film transistor (TFT) device, namely the inverted staggered type. Fabrication technique of the IT 1\' device was to deposit a-SiN:H (3000 A thickness, as an insulator layer) and a-Si:H (1500 A thickness, as a semiconductor layer) on surface of TCO (Transparent Conducting Oxide) coated SnO2 (as a gate contact) and then to be coated aluminum as a source and drain contact on top. Measurement of the output characterization exhibited comparison of Ion and Toff of 106 Key words : a-Si:H, a-SiN:H, \'I\'FT\', conductivity, FT-ER, XRD.